2007
DOI: 10.1063/1.2711435
|View full text |Cite
|
Sign up to set email alerts
|

Pressure driven flow of polymer solutions in nanoscale slit pores

Abstract: Polymer solutions subject to pressure driven flow and in nanoscale slit pores are systematically investigated using the dissipative particle dynamics approach. We investigated the effect of molecular weight, polymer concentration and flow rate on the profiles across the channel of the fluid and polymer velocities, polymers density, and the three components of the polymers radius of gyration. We found that the mean streaming fluid velocity decreases as the polymer molecular weight or/and polymer concentration i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 36 publications
5
35
0
Order By: Relevance
“…Specifically, for weakly confined chains ͑H / R g Ͼ 5, where H is the channel height and R g is the chain radius of gyration͒, chain migration was noted to be away from the walls; on the other hand, for strongly confined chains ͑H / R g Ͻ 3͒, the chains were found to migrate toward the wall in a flowing solution. 15,17,20,22,23 Consistent with the experimental studies noted earlier, BD simulations carried out by Hernandez-Ortiz et al 18 indicated that the degree of chain migration in flowing polymer solutions decreases as chain concentration becomes greater than 0.1C * . The cross stream migration of chains in flowing polymer solutions has also been predicted by kinetic theory.…”
Section: Introductionsupporting
confidence: 68%
“…Specifically, for weakly confined chains ͑H / R g Ͼ 5, where H is the channel height and R g is the chain radius of gyration͒, chain migration was noted to be away from the walls; on the other hand, for strongly confined chains ͑H / R g Ͻ 3͒, the chains were found to migrate toward the wall in a flowing solution. 15,17,20,22,23 Consistent with the experimental studies noted earlier, BD simulations carried out by Hernandez-Ortiz et al 18 indicated that the degree of chain migration in flowing polymer solutions decreases as chain concentration becomes greater than 0.1C * . The cross stream migration of chains in flowing polymer solutions has also been predicted by kinetic theory.…”
Section: Introductionsupporting
confidence: 68%
“…The DPD results of worm-like chains under shear flow matched well with the single DNA experiments (Symeonidis et al 2005). Millan et al (2007) studied the effects of bead number, polymer concentration, and flow rate on the streaming of polymer solution in pressure driven flow. Employing two-dimensional DPD simulations, the effects of field strength, chain length, solvent quality, and pore size were explored for the translocation of a single polymer chain through a pore under a fluid field (He et al 2007).…”
Section: Entropic Trapping: Theoretical and Numerical Backgroundsupporting
confidence: 51%
“…18 It has long been regarded as a wellunderstood problem, 29,30 since it can be studied by a variety of known procedures, including methodology in analogy with the diffusion problem in the presence of absorbing boundaries, [31][32][33][34][35][36][37][38] Monte Carlo calculations, [39][40][41] and novel mesoscopic simulation techniques such as Brownian dynamics ͑BD͒, 42,43 Lattice Boltzmann, 44,45 and dissipative particle dynamics ͑DPD͒. 46,47 It has been found that the theoretically calculated depletion profiles agree, in general, with the available experimental data. 48,49 They are concentration dependent [50][51][52][53] and coupled at flow conditions to the hydrodynamic interaction between polymers and the confining geometry.…”
Section: Introductionmentioning
confidence: 90%